Double diffusion natural convection in a square cavity filled with nanofluid - Chen, Sheng; Yang, Bo; Luo, Kai H.; Xiong, Xiaopeng; Zheng, Chuguang (Elsevier, 2016)
Double diffusive natural convection of nanofluid is commonly found in renewable energy engineering. However, nowadays our understanding on its fundamental characteristics is still limited. Especially, three crucial questions on its fundament have not been answered yet: (1) its performance not only in laminar regimes but also beyond laminar regimes, (2) the influence of the ratio of buoyancy forces on heat and mass transfer, (3) the correlation among the dimonsionless quantities which describe the features of this kind of convection. The present work tries to reveal the characteristics of double diffusive natural convection of nanofluid over a wide range, from laminar regimes to turbulent regimes, with the aid of numerical experiments. It is observed that the behavior of nanofluid in the laminar regimes is different from that in the turbulent regimes. Some conclusions presented in previous literature for laminar double diffusive of nanofluid may be invalid in its turbulent counterpart. The effect of the ratio of buoyancy forces on heat and mass transfer of nanofluid possesses some similarities with the pure base fluid as well as some obvious differences. Especially, a power-like correlation among the Nusselt number, Sherwood number, Rayleigh number, ratio of buoyancy forces and nanoparticle volume fraction has been extracted for the first time through our numerical experiments.